Survey on Various Types and Causes of Stress: Understanding the impact of stress on physical and mental well-being (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Biochemical parameters such asepinephrine and adrenal steroids, (ii) physiological parameters such as heart rate and blood pressure and (iii) behavioral effects such as anxiety, fear and tension. In essence, stressis an umbrella term that encompasses physical trauma, strenuous exercise, metabolicdisturbances and anxiety as they produce challenges to the body's homeostasis.The wear and tear that stressors subject our body too is termed as stress.“Stress is how people react to demands placed on them and arises when there isworry about one's capacity to cope. Seventy-five to 90 per cent of adult visitsto primary care physicians are for stress-related problems." For the layperson, however, the word stress has mental rather than physiologicalconnotations. As Anandi Iyer, Deputy Director at German Technical Cooperation(GTZ) says: "Stress occurs when you are incapable of handling a givensituation. For instance, for soldiers constantly at the border, the situationis no longer so stressful. But for others, it would be."